Foreign direct investment and U.S. national security: CFIUS under the Obama Administration - Mark E. Plotkin; David N. Fagan (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2010)
The Committee on Foreign Investment in the United States review process slowed during the inaugural year of the Obama Administration. The authors examine the origins of this shift and suggest actions that parties can take to facilitate the process.
Keywords: 330